2019
DOI: 10.30848/pjb2019-3(30)
|View full text |Cite
|
Sign up to set email alerts
|

Functional, antioxidant, antimicrobial potential and food safety applications of Curcuma longa and Cuminum cyminum

Abstract: Turmeric (Curcuma longa) and Cumin (Cuminum cyminum) seeds are common spices used in foods and are necessary commodity of kitchens. They have known potential in health and pharmacentical industries. In present study, we explored the antibacterial, antifungal, antioxidant and functional properties of turmeric and cumin seeds extracts. The extracts were also used against Escherichia coli in active packaging for pathogen control and food safety. It was found in the study that, phlobatannins, flavonoids, alkaloids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 30 publications
(34 reference statements)
0
19
0
Order By: Relevance
“…For example, it is documented that C. longa has growth inhibiting properties against different bacteria like, Salmonella typhi and S. aurous. 30 We found that T. ammi possessed antibacterial properties against S. aureus at all provided concentrations (5%, 10% and 15%). These results are coherent with the study that described the antimicrobial activity of this spice against S. aureus and E. coli.…”
Section: Discussionmentioning
confidence: 69%
“…For example, it is documented that C. longa has growth inhibiting properties against different bacteria like, Salmonella typhi and S. aurous. 30 We found that T. ammi possessed antibacterial properties against S. aureus at all provided concentrations (5%, 10% and 15%). These results are coherent with the study that described the antimicrobial activity of this spice against S. aureus and E. coli.…”
Section: Discussionmentioning
confidence: 69%
“…In maceration extraction, 200 g of fine grounded powder was used for extraction using 2 L ethanol as solvent with 1:10 ratio, following standard procedures described by Akbar et al (2019a) . The process was conducted in a dark room to avoid light exposure.…”
Section: Methodsmentioning
confidence: 99%
“…The antibacterial activity of B. baluchistanica bark, leaf, and root extracts was determined by using agar well diffusion method ( Akbar et al, 2019a ). Freshly prepared sterilized culture media were inoculated with the target bacterial strains ( Bacillus subtilis , Bacillus licheniformis , Escherichia coli , Klebsiella pneumoniae , Pseudomonas aeruginosa , Rhodococcus erythropolis , Salmonella typhi , and Staphylococcus aureus ) and incubated at 37°C for 24 h. The target bacterial cultures were spread over the surface of sterilized Muller Hinton Agar (Oxoid, UK) plates with the help of a sterilized cotton swab for the determination of antibacterial activity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Curcumin is the main active ingredient and is well known for its use in food industry as preservative and colouring agent. It is also belived as potential antimicrobial, antioxidant and antiinflammatory agent (Han et al, 2018;Akbar et al, 2019;Praditya et al, 2019). It has also been tested previously against Chikungunya virus, Zika virus, human immunodeficiency virus (HIV) and influenza type A (Dai et al, 2018).…”
Section: Introductionmentioning
confidence: 99%